Preparation of TiO2 nanoparticles via cathode glow discharge electrolysis and its photocatalytic performance in the degradation of methylene blue. Issue 6 (20th February 2022) - Lu, Quanfang; Li, Juanlong; Wang, Bo; Yu, Jie; Ma, Xiaojuan; Cui, Lijuan; Feng, Yan
Abstract: TiO2 nanoparticles (NPs) were prepared by cathode glow discharge electrolysis in sodium fluoride solution, in which cetyltrimethyl ammonium bromide (CTAB) acted as a stabilizer, and a Ti foil and a Pt needlepoint served as the anode and the cathode, respectively. The structure, component, and morphology of TiO2 NPs were characterized. A possible preparation mechanism was proposed. In addition, the photocatalytic performance of TiO2 NPs was assessed through the degradation of methylene blue (MB). The results showed that TiO2 NPs with 12.7 nm particle size could be prepared at 500 V discharge voltage. CTAB, as a stabilizer, can diminish the agglomeration. The photocatalytic property of TiO2 NPs for the degradation of MB with 0.15% CTAB is markedly superior to that of TiO2 NPs without adding CTAB and commercial TiO2 NPs (P25). Abstract : TiO2 nanoparticles were prepared in a sodium fluoride solution containing cetyltrimethyl ammonium bromide at 500 V discharge voltage via cathode glow discharge electrolysis, in which a Ti foil and a Pt needle served as the anode and the cathode, respectively.